Yoga Gymnastics Training for Primigravida Pregnant Women in the Third Trimester - Sitorus, Riris; Damayanti, Grace Erlyn; Ginting, Samuel (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
Pregnancy is a process in which a woman carries a fetus after it occurs. In the process of labor, anxiety often arises in the prospective mother so it is recommended that the mother do light exercise such as yoga. Yoga is a recommended choice in preparation for labor, because this exercise is able to control breathing and relax the mind. Yoga breathing exercises will accelerate the blood flow rate so that oxygen is fulfilled for the mother and her fetus. In addition, yoga is also able to control anxiety so that it can achieve better health during childbirth. Training activities were given to 20 pregnant women participants at the Matahari clinic. The increase in knowledge of PkM participants was assessed based on the average pre- and post-test scores after being given material, demonstrations, and direct training. Yoga exercises for pregnant women were carried out based on standard SOPs, which were assisted by the PkM team in their implementation. The results of the training showed that PkM participants were able to carry out yoga exercises according to the SOP. In addition, participants also received direct benefits in the form of physical and mental health. Through this training, it can also be seen that there has been an increase in participants' knowledge about yoga exercises in overcoming anxiety with a pre-test score of 5.95 to a post-test score of 7.55. Yoga exercises have been proven to improve participants' knowledge and skills in carrying out yoga exercises which are useful in maintaining health and controlling anxiety when giving birth.